2019
DOI: 10.1016/j.pnpbp.2018.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Cortical thickness in major depressive disorder: A systematic review and meta-analysis

Abstract: Neuroimaging studies assessing neurobiological differences between patients with major depressive disorder (MDD) and healthy controls (HC) are often hindered by small sample sizes and heterogeneity of the patient sample. We performed a comprehensive literature search for studies assessing cortical thickness between patient and control groups, including studies investigating treatment effects on cortical thickness. We identified 34 studies meeting criteria for the systematic review and used Seed-based d Mapping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
71
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(88 citation statements)
references
References 108 publications
15
71
2
Order By: Relevance
“…The most important feature for predicting depression symptoms was IC0, which involves complex covarying patterns of low GMD and cortical thickness in mainly temporal but also frontal regions. This pattern is largely in line with previous research (Lai, ; Schmaal et al, ; Suh et al, ). IC0 also encompassed high FA and low MD and RD in interhemispheric connections and frontal–striatal thalamic pathways, in line with previous studies, albeit in the opposite direction (Chen et al, ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The most important feature for predicting depression symptoms was IC0, which involves complex covarying patterns of low GMD and cortical thickness in mainly temporal but also frontal regions. This pattern is largely in line with previous research (Lai, ; Schmaal et al, ; Suh et al, ). IC0 also encompassed high FA and low MD and RD in interhemispheric connections and frontal–striatal thalamic pathways, in line with previous studies, albeit in the opposite direction (Chen et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…A host of studies across a range of neuroimaging modalities have implicated various brain regions and networks in depression. Metaanalyses of structural magnetic resonance imaging (MRI) studies have suggested thinner orbitofrontal and anterior cingulate cortex in patients with depression compared to healthy controls (Lai, 2013;Schmaal et al, 2017;Suh et al, 2019). A large-scale meta-analysis comprising 2,148 patients and 7,957 controls from 20 different cohorts reported slightly smaller hippocampal volumes in patients with depression compared to controls (Schmaal et al, 2016), but the overall pattern of results suggested substantial heterogeneity and otherwise striking similarity across groups for all other investigated subcortical structures (Fried & Kievit, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a study reports an absence of increased volume of BG also for typical antipsychotics (Kreczmanski et al, 2007); fourth, anticonvulsant drugs, used in the treatment of bipolar disorder but also for epilepsy (the only neurologic disease with a non-negligible number of experiments in our database) showed to produce decreases or no effect (Chang et al, 2009;Germaná et al, 2010;Abé et al, 2016;Hibar et al, 2018); fifth, the increased striatal volume of relatives of schizophrenic patients suggests a genetic factor (Oertel-Knöchel et al, 2012). Similarly, increased cortical thickness and subcortical volume were found also in drug-naive patients with depression (Qiu et al, 2014;Reynolds et al, 2014;Yang et al, 2015;Zuo et al, 2018;Li et al, 2019;Suh et al, 2019); sixth, patients with autism or development disorders included in our study were not under drug treatment (Table S4).…”
Section: Discussionsupporting
confidence: 74%
“…The most important feature for predicting depression symptoms was IC0, which involves complex covarying patterns of low GMD and cortical thickness in mainly temporal but also frontal regions. This pattern is largely in line with previous research (Lai, 2013;Schmaal et al, 2017;Suh et al, 2019). IC0 also encompassed high FA and low MD and RD in interhemispheric connections and frontal-striatal thalamic pathways, in line with previous studies, albeit in the opposite direction (Chen et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…A host of studies across a range of neuroimaging modalities have implicated various brain regions and networks in depression. Meta-analyses of structural magnetic resonance imaging (MRI) studies have suggested thinner orbitofrontal (OFC) and anterior cingulate cortex (ACC) in patients with depression compared to healthy controls (Lai, 2013;Schmaal et al, 2017;Suh et al, 2019). A large-scale meta-analysis comprising 2148 patients and 7957 controls from 20 different cohorts reported slightly smaller hippocampal volumes in patients with depression compared to controls (Schmaal et al, 2016), but the overall pattern of results suggested substantial heterogeneity and otherwise striking similarity across groups for all other investigated subcortical structures (Fried & Kievit, 2016).…”
Section: Introductionmentioning
confidence: 99%